Utilization of Metaphor as a Method of Language Teaching - Poghosyan, Ofelya (Armenian Folia Anglistika, 2013)
Metaphor is often used as a stylistic device in literature to exert aesthetic impact on the reader. Nonetheless, due to its underlying cognitive function, metaphor can easily be used in the language teaching process to develop the creative mind of the learner/teacher, as well as to increase the efficiency of the teaching process.